The therapeutic potential of bone marrow‐derived mesenchymal stromal cells on hepatocellular carcinoma. (21st October 2013) - Bayo, Juan; Marrodán, Mariano; Aquino, Jorge B.; Silva, Marcelo; García, Mariana G.; Mazzolini, Guillermo
Abstract Mesenchymal stromal cells (MSCs) are more often obtained from adult and extraembryonic tissues, with the latter sources being likely better from a therapeutic perspective. MSCs show tropism towards inflamed or tumourigenic sites. Mechanisms involved in MSC recruitment into tumours are comprehensively analysed, including chemoattractant signalling axes, endothelial adhesion and transmigration. In addition, signals derived from hepatocellular carcinoma (HCC) tumour microenvironment and their influence in MSC tropism and tumour recruitment are dissected, as well as the present controversy regarding their influence on tumour growth and/or metastasis. Finally, evidences available on the use of MSCs and other selected progenitor/stem cells as vehicles of antitumourigenic genes are discussed. A better knowledge of the mechanisms involved in progenitor/stem cell recruitment to HCC tumours is proposed in order to enhance their tumour targeting which may result in improvements in cell‐based gene therapy strategies.